Hepatoprotective Effects of Glibenclamide, Catechin, and Ethanolic Neem Leaf Extract in Alloxan-Induced Diabetic Rats - Olusoji A. Oyesola; Oluwaseye Emmanuel Olayemi; Olaniyi A. Soetan; Temitope E. Ogungbenle; Solomon O. Adebanjo; Eunice O. Ojo-Adebayo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2026)
Background: Diabetes mellitus is a systemic disorder that causes hepatic damage, primarily through oxidative stress and inflammation. This study evaluated the hepatoprotective effects of glibenclamide, catechin, and ethanolic neem leaf extract in alloxan-induced diabetic male rats.Methods: Fifty Sprague-Dawley rats were allocated into five groups: normal control, diabetic control, and three treatment groups receiving glibenclamide (5 mg/kg), catechin (40 mg/kg), or neem extract (250 mg/kg) orally for 14 days after diabetes induction (alloxan, 150 mg/kg i.p.). Diabetes was confirmed by a fasting blood glucose level ≥200 mg/dL after 72 h. Liver function biomarkers (AST, ALT, ALP, albumin, bilirubin, and total protein), oxidative stress markers (MDA, SOD, CAT, and GSH), lipid profiles, and liver histopathology were evaluated.Results: Diabetic rats exhibited marked hyperglycaemia, elevated liver enzyme levels, lipid peroxidation, and hepatocellular damage. All treatments significantly improved glycaemic control, reduced hepatic enzyme levels and MDA, and enhanced antioxidant enzyme activities. Neem-treated rats demonstrated the most significant biochemical recovery and near-normal liver histology with preserved Kupffer cells.Conclusion: These findings suggest that neem leaf extract exerts robust hepatoprotective effects, likely because of its high polyphenolic content and antioxidant properties, making it a promising candidate for mitigating liver injury in diabetes mellitus